Solution of methodological problems in selection of methods of euthrophic water bodies’ rehabilitation - Aleksandr N. Popov; Valery F. Mukhutdinov (Водное хозяйство России: проблемы, технологии, управление)
In the conditions of the economic activities intensification the problem of choice of the optimal measures for water bodies’ rehabilitation becomes more relevant, therefore improvement of scientific/methodological support of water/economic and water/protective activities acquires special significance. However, at present in Russia there is no single algorithm and method for pre-design engineering/ecological surveying, no recommendations on optimal choice of rehabilitation methods for a specific water body with taking into account the whole integrity of impact and connections of aquatic, ground, and aerial ecosystems, as well as anthropogenesis. Experts of RosNIIVKH have developed a number of manuals that enable at the stage of pre-design surveying to determine the optimal set of rehabilitation measures for a water body, to assess the necessary and sufficient degree of realization of each of them to attain the pre-set objective, and to forecast the water body state. A draft of the “Manual on selection of optimal methods of euthrophic water bodies’ rehabilitation” is one of these documents. It was tested at seven lakes and twelve reservoirs. During the testing, we faced a number of methodological problems that are to be solved to simplify these methods and to make them more efficient.